New technological possibilities to prepare InP epitaxial layers, as well as ohmic and barrier contacts to them, and the properties of microwave diodes made on their basis - Arsentyev, I.N.; Bobyl, A.V.; Tarasov, I.S.; Shishkov, M.V.; Boltovets, N.S.; Ivanov, V.N.; Kamalov, A.B.; Konakova, R.V.; Kudryk, Ya.Ya.; Lytvyn, O.S.; Lytvyn, P.M.; Markovskiy, E.P.; et al. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
A novel technological approach to fabrication of n-InP autoepitaxial films LPE-grown on porous n⁺-InP substrates, as well as ohmic and barrier contacts to them using (quasi)amorphous TiBx interstitial phases, is proposed. We demonstrate the advantages of TiBx−n-n⁺-n⁺⁺-InP Schottky-barrier diodes made on porous substrates over those made on the standard rigid substrates, as well as the possibility to make Gunn diodes (intended for the 120−150 GHz frequency range) on the InP epitaxial structures grown on porous substrates.